Pelatihan Tahsin Calon Imam Lansia di Masjid Darussalam Perumahan Griya Perwita Wisatas Sleman: Indonesia - Ashadi, Willi; Munzilin, Khairul (UII, 2026)
This community service activity aims to improve the ability to read the Qur'an in accordance with the rules of tajwid and prepare prospective elderly imams at the Darussalam Mosque, Griya Perwita Wisata Housing Complex, Ngaglik District, Sleman Regency, to lead prayers. The high participation of elderly congregants has not been matched by adequate Quran reading skills due to differences in religious education backgrounds, declining cognitive abilities, and the absence of elderly-friendly tahsin programs. The implementation method consists of three stages, namely identification and initial assessment of Quran reading ability with categories of very low, low, and moderate, structured tahsin training through small halaqah, talaqqi, and musyafahah methods, as well as evaluation and follow-up assistance through practice as prayer leaders. This program was supported by competent resource persons such as Ust Hariono and Ust Slamet as regular speakers at the Darussalam Mosque. The informants and note-takers for this activity were Willi Ashadi and Khairul Munzilin, lecturers in the International Relations study program at UII, together with community service students named Mahadir. The results of the activity show that 90% of participants experienced an increase in their ability to read the Qur'an and showed significant progress in tahsin learning, as well as the formation of a sustainable tahsin halaqah group. Overall, the tahsin training and prayer leader coaching program for the elderly was effective and contributed to the social and religious empowerment of the elderly congregation based in the mosque community.